2018
DOI: 10.2174/1871529x18666180326121239
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation Polymorphisms in Ischemia

Abstract: In this review, we have evaluated the role of polymorphisms involved in platelet activation and development of ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…In this regard, an association between rs1131882, rs4311994 and rs3779647 and increased platelet activity in diabetic patients on aspirin therapy has already been reported (Postula et al, 2011;Postula et al, 2013). Studies also indicated that the presence of genetic variations in the COX-2 gene such as rs5275 boosts COX-2 expression and therefore aid in reducing the risk of myocardial infarction and ischemia; cardiac conditions in which platelet activation makes an important contribution (Haybar et al, 2018). rs4251961 was associated with higher expression of fibrinogen that plays a key role in hemostasis, and thus participates in the prevention of bleeding (Wassel et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, an association between rs1131882, rs4311994 and rs3779647 and increased platelet activity in diabetic patients on aspirin therapy has already been reported (Postula et al, 2011;Postula et al, 2013). Studies also indicated that the presence of genetic variations in the COX-2 gene such as rs5275 boosts COX-2 expression and therefore aid in reducing the risk of myocardial infarction and ischemia; cardiac conditions in which platelet activation makes an important contribution (Haybar et al, 2018). rs4251961 was associated with higher expression of fibrinogen that plays a key role in hemostasis, and thus participates in the prevention of bleeding (Wassel et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…In conclusion, although SerpinB2 has classically been associated with inhibition of uPA-mediated fibrinolysis, we illustrate herein that SerpinB2 (at least in mice) has an unexpected plateletassociated activity in the regulation clot formation. Further research is required to ascertain how relevant this new role for SerpinB2 might be in human diseases [6,9,[41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of a number of molecules protecting the cardiac tissue after injury is regulated by different signaling pathways (Deb, ; Haybar, Khodadi, Shahjahani, & Saki, ; Haybar, Khodadi, Zibara, & Saki, ). HSF1 is a molecule expressed after damage to cardiomyocytes or other cardiac cell populations, which prevents cardiac dysfunction and leads to homeostasis through HSPs expression (Krishnamurthy, Vedam, Kanagasabai, Druhan, & Ilangovan, ; Peng et al, ).…”
Section: Discussion and Future Perspectivementioning
confidence: 99%